Executive council of the SPF, f.l.t.r.: ?, ?, Wahlquist, Södermann, Eriksson, Ahldin, ?, Sandberg - Ekstedt, Einar,
Executive council of the SPF, f.l.t.r.: ?, ?, Wahlquist, Södermann, Eriksson, Ahldin, ?, Sandberg.